Hydrogels Based on Starch from Various Natural Sources: Synthesis and Characterization. (12th June 2021) - Kalendova, Petra; Svoboda, Ladislav; Hroch, Jan; Honcova, Pavla; Drobna, Helena; Slang, Stanislav
Abstract: Hydrogels based on a graft copolymer of acrylic acid (AA) and acrylamide (AAm) on a backbone of starch, obtained from different natural sources, have been prepared and characterized for potential agricultural use, as soil moisture regulators and nutrient sources for plant nutrition. Five types of starch are used: corn, waxy corn, wheat, potato, and rice starch. Hydrogels are prepared by a solution polymerization method, in the presence of ammonium persulphate (PSA) as initiator and N, N' ‐methylene‐bis‐acrylamide (MBA) as a cross‐linking agent. Thermal and physico‐chemical properties, such as thermogravimetry analysis and differential scanning calorimetry data and swelling properties of hydrogels, are observed. The influences of the cross‐linking agent on the swelling ratio (SR) and solubility of prepared hydrogels are studied and optimized. The highest SR observed in water corresponded to non‐cross‐linked hydrogels prepared with waxy corn starch (780 g water per g dry matter), and the SR of these hydrogels in ammonium sulfate and calcium nitrate solutions are 9.6 and 1.2 g per g dry matter, respectively. Higher thermal stability is observed with cross‐linked starch‐g‐(AA‐AAm) hydrogels. The non‐cross‐linked hydrogels have a higher SR, but also have significant solubility in water. Abstract : Hydrogels based on a graft copolymer of acrylic acid and acrylamide on a backbone of starch from five natural sources are synthesized. The water absorbency is from 500 to 800 g of water per g of dry matter and absorption of inorganic solutions is lower in comparison with urea solution uptake. The hydrogels can be used as soil moisture regulators and urea nitrogen fertilizers.